Visual attention and phonological processing in children with developmental language disorder - Lara-Díaz, María Fernanda; Beltrán Rojas, Judy Costanza; Aponte Rippe, Yennifer (Frontiers in Communication, 2024)
Introduction: Developmental Language Disorder (DLD) is a neurobiological condition characterized by insufficient language and communication development, with no underlying physical, sensory, or cognitive explanations. A prominent feature among children with DLD is their struggle with phonological processing, a pivotal skill for later reading proficiency. Recent research suggests that children with DLD may also exhibit impairments in various non-linguistic cognitive abilities, including memory, attention, and perception. Of particular importance is visual attention, which plays a critical role in integrating visual perceptual information with diverse cognitive and linguistic processes.Objective: To characterize visual attention during phonological processing tasks in Colombian children with DLD.Methodology: This study employed a cross-sectional descriptive experimental design involving 20 children diagnosed with Developmental Language Disorder (DLD) and 20 children without language difficulties. All participants underwent language, vocabulary, and phonological awareness tests. Additionally, an experimental task utilizing the eye-tracking method was designed and administered to measure phonological processing with phonological and lexical distractors.Results: Children with DLD exhibited diminished performance on phonological awareness tasks, as evidenced by their lower scores. This was further supported by the experimental phonological processing task, where an interference effect was observed in the presence of lexical distractors for word recognition, but not with phonological distractors. Conclusions: Children with DLD demonstrated deficiencies in both phonological awareness and visual attention skills during linguistic and phonological processing tasks. They also exhibit reduced sensitivity in identifying phonological relations such as rhyme. The study discusses these findings along with their clinical implications, emphasizing the importance of assessing online processing abilities in children with DLD and considering the influence of other cognitive abilities on their linguistic performance.